Analisis Pengaruh Variabel Makroekonomi Terhadap Jakarta Islamic Index - Raka Abidzar Al Ghifari; Kristianingsih Kristianingsih; Destian Arshad Darulmalshah Tamara (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the effect of macroeconomic factors on the JII during the 2015-2019 period. Macroeconomic factors in this study include the rate of return for Bank Indonesia Sharia Certificates (SBIS), the IDR / USD Exchange Rate, and Inflation. The data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange and the official website of Bank Indonesia. The type of data used is quantitative data. All variable data taken is in the form of monthly time series data from January 2015 to December 2019. This research is a quantitative study with a descriptive approach. The method used in this research is multiple linear regression using the WarpPLS 7.0 program. The results of this study indicate that partially rate of return for Bank Indonesia Syariah Certificates (SBIS), IDR/USD exchange rate, and inflation have a negative and significant effect on the JII.